1999
DOI: 10.1007/s002040050607
|View full text |Cite
|
Sign up to set email alerts
|

Increase in urinary excretion of 6β-hydroxycortisol in common marmosets as a marker of hepatic CYP3A induction

Abstract: The ratio of urinary 6beta-hydroxycortisol (6beta-OHF) to free cortisol (F), i.e., the 6beta-OHF/F ratio, has been reported to be a specific marker for human CYP3A induction by in vivo studies of human subjects. In the development of drugs, it is quite beneficial to predict human CYP3A induction in preclinical safety studies using urine samples from experimental animals. We examined the 6beta-OHF/F ratio in urine of common marmosets administered with rifampicin, a potent inducer of CYP3A, to evaluate the usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cytochrome P450 3A4 is the major drug metabolising enzyme [25], which catalyses the biotransformation of quinine to 3-hydroxyquinine. A known marker for induction of hepatic cytochrome P450 3A4 is 6β-hydroxycortisol formation [26][27][28][29]. Using this marker studies performed in pregnant women have shown a significant increase in the formation of this metabolite during pregnancy in comparison to postpartum [30] indicating higher activity of CYP3A.…”
Section: As Shown Inmentioning
confidence: 99%
“…Cytochrome P450 3A4 is the major drug metabolising enzyme [25], which catalyses the biotransformation of quinine to 3-hydroxyquinine. A known marker for induction of hepatic cytochrome P450 3A4 is 6β-hydroxycortisol formation [26][27][28][29]. Using this marker studies performed in pregnant women have shown a significant increase in the formation of this metabolite during pregnancy in comparison to postpartum [30] indicating higher activity of CYP3A.…”
Section: As Shown Inmentioning
confidence: 99%
“…The enzyme is expressed along with the glucocorticoid receptor (GR), and thereby regulates glucocorticoid (GC) activity. Substantial amounts of 11β‐HSD1 are found in the human liver, adipose tissue, gonad, brain, pituitary and vascular smooth muscle 3–5 . 11β‐HSD type 2 (11β‐HSD2) is found in the same organs as the mineralocorticoid receptor (MR).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme 6β‐hydroxylase is also responsible for cortisol metabolism, albeit only for a very small part of it (an estimated 1% of the overall cortisol metabolism) 1 . Through this pathway, cortisol is excreted into the urine in the form of 6β‐hydroxycortisol (6β‐OHF), a metabolite also used as an index of the activity of cytochrome P450 (CYP) 3A4 in the liver 4,10 . In addition, some cortisol (F) and cortisone (E) is excreted into the urine without prior metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation